2023
DOI: 10.1097/gox.0000000000005005
|View full text |Cite
|
Sign up to set email alerts
|

The Peripheral Nerve Surgeon’s Role in the Management of Neuropathic Pain

Seamus P. Caragher,
Kimberly S. Khouri,
Floris V. Raasveld
et al.

Abstract: Summary: Neuropathic pain (NP) underlies significant morbidity and disability worldwide. Although pharmacologic and functional therapies attempt to address this issue, they remain incompletely effective for many patients. Peripheral nerve surgeons have a range of techniques for intervening on NP. The aim of this review is to enable practitioners to identify patients with NP who might benefit from surgical intervention. The workup for NP includes patient history and specific physical examination maneuvers, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…One such technique is targeted muscle reinnervation (TMR), where a nerve end is coaptated to a terminal motor nerve branch of a muscle that is in close proximity. [2][3][4] As a relatively novel modality, TMR has gained popularity for the treatment of these sequela and its utilization as a prophylactic modality is being more widely adopted across the United States. 5 However, it has been identified that access to this technique at time of amputation (primary TMR) is not always available for many geographical locations.…”
Section: Introductionmentioning
confidence: 99%
“…One such technique is targeted muscle reinnervation (TMR), where a nerve end is coaptated to a terminal motor nerve branch of a muscle that is in close proximity. [2][3][4] As a relatively novel modality, TMR has gained popularity for the treatment of these sequela and its utilization as a prophylactic modality is being more widely adopted across the United States. 5 However, it has been identified that access to this technique at time of amputation (primary TMR) is not always available for many geographical locations.…”
Section: Introductionmentioning
confidence: 99%